PUBLIC ADMINISTRATION POLICIES IN FIRE FIGHTING VOLUNTEERING IN GALICIA AND MODERN PRAXIS OF FIRE FIGHTING VOLUNTEERING IN EUROPEAN UNION COUNTRIES - Gontar Z.G. (Pressing Problems of Public Administration, 2015)
This article offers a research on the role and importance of historic experience in fire fighting volunteering and related public administration policies in Galicia and European Union countries. It also analyzes their impact on current condition of fire safety for the population of Ukraine.